2020
DOI: 10.1021/acsapm.9b01223
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Conductive and Thermally Stable Ionic Liquid Gel Electrolyte for Calcium-Ion Batteries

Abstract: Calcium-ion batteries are promising alternatives for post-lithium-ion batteries. However, their progress remains limited by challenges associated with the development of stable and effective electrolytes. We report for the first time an ionic liquid polymer gel membrane as both the electrolyte and the separator for use in a calcium-ion battery operating at room temperature. The membrane is prepared via single-step photo-cross-linking of poly(ethylene glycol) diacrylate in the presence of calcium salt dissolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 63 publications
2
50
0
Order By: Relevance
“…The as-prepared IL-based gel exhibited outstanding durability while utilized in a skin-like sensor under harsh environmental conditions. Meanwhile, Biria’s team described the preparation of a highly conductive IL-based gel electrolyte via photopolymerization using a mixture of PEGDA polymer and camphorquinone and (4-octyloxyphenyl)phenyliodonium hexafluoroantimonate) as the photoinitiator in 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF 4 ) containing calcium salt as solvent [ 40 ]. Recently, in 2019, Rana et al synthesized an ultradurable double network (DN) IL-based gel composed of densely cross-linked polyvinyl alcohol (C-PVA) as the first network and coarsely cross-linked poly(2-hydroxyethyl methacrylate) (C-pHEMA) as the second network in EMIMBF 4 as solvent and K 2 S 2 O 8 as initiators via a two-step, thermally-initiated, free-radical polymerization [ 41 ].…”
Section: Preparation Of Il-based Gelmentioning
confidence: 99%
See 1 more Smart Citation
“…The as-prepared IL-based gel exhibited outstanding durability while utilized in a skin-like sensor under harsh environmental conditions. Meanwhile, Biria’s team described the preparation of a highly conductive IL-based gel electrolyte via photopolymerization using a mixture of PEGDA polymer and camphorquinone and (4-octyloxyphenyl)phenyliodonium hexafluoroantimonate) as the photoinitiator in 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF 4 ) containing calcium salt as solvent [ 40 ]. Recently, in 2019, Rana et al synthesized an ultradurable double network (DN) IL-based gel composed of densely cross-linked polyvinyl alcohol (C-PVA) as the first network and coarsely cross-linked poly(2-hydroxyethyl methacrylate) (C-pHEMA) as the second network in EMIMBF 4 as solvent and K 2 S 2 O 8 as initiators via a two-step, thermally-initiated, free-radical polymerization [ 41 ].…”
Section: Preparation Of Il-based Gelmentioning
confidence: 99%
“…For the first time, liquid GPEs were used as electrolytes and separators in Ca-ion batteries at room temperature. Biria et al [ 40 ] prepared an electrolyte solution of Ca perchlorate salt (Ca(ClO 4 ) 2 ), Ca-tetrafluoroborate (Ca(BF 4 ) 2 ), and Ca bis-(trifluoromethylsulfonyl)imide (Ca(TFSI) 2 ) dissolved in 1-ethyl-3-methylimidazolium trifluoromethanesulfonate (EMIMTFMS) to mix with 2.5% poly(ethylene glycol) diacrylate-photoinitiator camphorquinone (PEGDA-CQ) and 1.5% 4-octyloxyphenyl)phenyliodonium hexafluoroantimonate (4OPP-HFA) as a photoinitiator system, and then injected them into a Teflon ring cell and exposed them to a light emitting diode (LED) to form a gel. They reported ionic conductivity at room temperature between 10 −4 and 10 −3 S cm −1 , stability of up to 4 V, a cationic transfer rate of 0.17, high thermal stability up to 300 °C, and an initial discharge capacity of 140 mAh g −1 .…”
Section: Applications Of Il-based Gelsmentioning
confidence: 99%
“… [44b] The polymer electrolyte loaded with calcium nitrate as the Ca 2+ source obtained rubber properties at room temperature and higher temperature, thus increasing the mobility of the polymer chain and increasing the ionic conductivity. Beside, an ionic liquid GPE with ionic conductivity between 0.1–1 mS cm −1 and thermal stability around 300 °C synthesized by single‐step cross‐linking of poly(ethylene glycol) diacrylate in the case of calcium salt dissolution in ionic liquid formed from 1‐Ethyl‐3‐methylimidazolium trifluoromethanesulfo‐nate and different calcium salts fully combines the advantages of ionic liquids and polymer electrolytes: high ionic mobility, strong thermal and mechanical stability, and good electrode‐electrolyte interface contact [44a] …”
Section: Gpes For Multivalent Ion Batteriesmentioning
confidence: 99%
“…Biria et al 209 presence of calcium salt dissolved in an ionic liquid. The prepared ILPGE by Biria et al 209 showed ionic conductivities between 10 À4 and 10 À3 S/cm at room temperature, ESW~4 V vs Ca/ Ca 2+ , a cationic transference number~0.17, good thermal stability up to~300 C, and a prototype battery delivered a promising initial discharge capacity of~140 mAh/g.…”
Section: Application Of Il-based Pes In Rechargeable Batteriesmentioning
confidence: 99%
“…Biria et al 209 presence of calcium salt dissolved in an ionic liquid. The prepared ILPGE by Biria et al 209 showed ionic conductivities between 10 À4 and 10 À3 S/cm at room temperature, ESW~4 V vs Ca/ Ca 2+ , a cationic transference number~0.17, good thermal stability up to~300 C, and a prototype battery delivered a promising initial discharge capacity of~140 mAh/g. Singh et al 210 developed a rechargeable lithium polymer battery consist IL-GPE 65 as a electrolyte that showed a high Li + -ion transference number and Li + ion conductivity (~0.43 and~1.6 Â 10-3 S/cm at RT).…”
Section: Application Of Il-based Pes In Rechargeable Batteriesmentioning
confidence: 99%